PENGARUH INTELLECTUAL CAPITAL PADA FINANCIAL PERFORMANCE PERUSAHAAN (Studi Empiris pada Perusahaan Infrastruktur, Utilitas, dan Transportasi yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2011) - Ivan Herdyanto; Mohamad Nasir (Diponegoro Journal of Accounting, 2013)
This study aims to examine the effect of intellectual capital on corporate financial performance. Independent variable used in this study is intellectual capital which measured by VAIC, while dependent variable are financial performance which consist of Return on Asset, Return on Equity, Asset Turnover and Growth Revenue.Sample of this study is the infrastructure, utilities, and transportation companies which listed in Indonesia Stock Exchange with sample period 2009-2011. Data collected by purposive sampling method. Sample used in this study were 28 companies each year. This study used simple linear regression for data analysis. This result showed that intellectual capital provides a positive and significant influence in Return on Asset, Return on Equity, and Asset Turnover. Intellectual capital don’t have significant influence in Growth Revenue.Overall, this study found that Capital Employed (VACA) gives the most contribution in creating value added and competitive advantages of the company.